Myofibroblasts impair myocardial impulse propagation by heterocellular connexin43 gap-junctional coupling through micropores - Tsuji, Yumika; Ogata, Takehiro; Mochizuki, Kentaro; Tamura, Shoko; Morishita, Yuma; Takamatsu, Tetsuro; Matoba, Satoaki; Tanaka, Hideo (Frontiers in Physiology, 2024)
Aim: Composite population of myofibroblasts (MFs) within myocardial tissue is known to alter impulse propagation, leading to arrhythmias. However, it remains unclear whether and how MFs alter their propagation patterns when contacting cardiomyocytes (CMs) without complex structural insertions in the myocardium. We attempted to unveil the effects of the one-sided, heterocellular CM-MF connection on the impulse propagation of CM monolayers without the spatial insertion of MFs as an electrical or mechanical obstacle.We evaluated fluo8-based spatiotemporal patterns in impulse propagation of neonatal rat CM monolayers cultured on the microporous membrane having 8μm diameter pores with co-culture of MFs or CMs on the reverse membrane side (CM-MF model or CM-CM model, respectively). During consecutive pacing at 1 or 2 Hz, the CM monolayers exhibited forward impulse propagation from the pacing site with a slower conduction velocity (θ) and a larger coefficient of directional θ variation in the CM-MF model than that in the CM-CM model in a frequency-dependent manner (2 Hz > 1 Hz). The localized placement of an MF cluster on the reverse side resulted in an abrupt segmental depression of the impulse propagation of the upper CM layer, causing a spatiotemporally non-uniform pattern. Dye transfer of the calcein loaded in the upper CM layer to the lower MF layer was attenuated by the gap-junction inhibitor heptanol. Immunocytochemistry identified definitive connexin 43 (Cx43) between the CMs and MFs in the membrane pores. MF-selective Cx43 knockdown in the MF layer improved both the velocity and uniformity of propagation in the CM monolayer. Conclusions: Heterocellular Cx43 gap junction coupling of CMs with MFs alters the spatiotemporal patterns of myocardial impulse propagation, even in the absence of spatially interjacent and mechanosensitive modulations by MFs. Moreover, MFs can promote proarrhythmogenic impulse propagation when in face-to-face contact with the myocardium that arises in the healing infarct border zone.